PENGARUH KUALITAS PELAYANAN DAN FASILITAS SEKOLAH TERHADAP KEPUTUSAN SISWA MEMILIH SEKOLAH PADA SMK WIYATA MANDALA KOTA BOGOR - Anis Kharimah Yulianti; Purwanti Purwanti (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
This study aims to determine the influence of service quality and school facilities on students' decisions in choosing SMK Wiyata Mandala in Bogor City, both partially and simultaneously. The research method used is an associative quantitative approach. The population in this study was 551 students of SMK Wiyata Mandala in Bogor City for the 2023-2024 academic year. The sampling technique used was purposive sampling with the Slovin formula. A total of 85 respondents were recruited. Data analysis methods used included instrument testing consisting of validity testing, reliability testing, classical assumption testing consisting of normality testing, multicollinearity testing, heteroscedasticity and autocorrelation testing, multiple linear regression testing, correlation coefficient testing, hypothesis testing consisting of partial t-tests and simultaneous f-tests, and coefficient of determination testing. The results of the study indicate that service quality has a positive and significant effect on student decisions with the regression equation Y = 10.479 + 0.747X₁ and a calculated t value of 10.687 which is greater than the t table of 1.989. School facilities also have a positive and significant effect on student decisions with the regression equation Y = 4.736 + 0.885X₂ and a calculated t value of 15.168 which is greater than the t table of 1.989. Simultaneously, service quality and school facilities have a positive and significant effect on student decisions with the regression equation Y = 3.114 + 0.228X₁ + 0.697X₂ and a calculated F value of 126.877 which is greater than the F table of 3.10. The R-square value (coefficient of determination) was 0.756, indicating that service quality and school facilities collectively contributed 75.6% to student decision-making, while the remaining 24.4% was influenced by other factors not examined. Based on these findings, it can be concluded that improving service quality, and particularly school facilities, is a crucial strategy for SMK Wiyata Mandala, Bogor City, to increase student interest and decision-making.